L’incantesimo della mimesis: poesia e filosofia tra essere stato e poter essere - Distaso, Leonardo V. (Bollettino Filosofico, 2017)
Forgetting the socratic vocation and the platonic sentence – the most difficult and risky task – also means stop explaining everything to the people, the same people who Plato wants to lead out to the cave, and who Socrates said was more able that poets to reason. Adorno broke this spell to find again the enchantment of poetry (after Auschwitz), beyond the communication announcing the impossibility of the same communication and bringing again the word to itself.